Key Aspects of German Business Law
VIII, 334 p. 57 illus.
Keywords: This book is the second edition of the well received Key Aspects of German Business Law. Due to the great number of changes in the German Civil Code and Tax Law, this edition is a particularly important and useful tool for those entering the German and European Union market. The book presents a clear and precise overview. It was written by attorneys involved in the daily practice of business law in Germany and the European Union, and is aimed at people who wish to orient themselves quickly with the German legal system and the manner in which it impacts business purchases, establishment, operations and liquidations. The first section of the book is devoted to an explanation of the major issues to be considered in acquiring or establishing a business in Germany, whereas the second section focuses on areas of special consideration. In both sections special attention has been paid to highlighting and explaining the differences between the German legal system and that of the United States, Though the intention is to provide information that will prove valuable to all foreigners, particularly business people and lawyers advising clients with an interest in doing business in Germany.